Transport of dispersed oil compounds to the seafloor by sinking phytoplankton aggregates: A modeling study. (February 2020) - Francis, S.; Passow, U.
Abstract: Up to 20% of the oil spilled as a result of the Deepwater Horizon explosion in the Gulf of Mexico in 2010 was deposited as degraded oil compounds on the seafloor. Much of that deposition was likely due to dispersed oil compounds having been integrated into fast-sinking aggregates, which transported it effectively to depth. Understanding the details of this oil transport mechanism, and predicting its potential magnitude, is important for the management and mitigation of future oil spills. The 1-D model described here simulates a) a diatom bloom and the resulting formation of aggregates via coagulation of cells, b) the scavenging of dispersed oil compounds by these aggregates as they sink through the water column, c) the degradation of diatom carbon and oil carbon during transit, and d) the ultimate deposition of aggregates and oil compounds to the seafloor. The model is parameterized using primarily field- and laboratory-collected data and the model results are compared to sediment trap data. Specifically, one large diatom sedimentation event observed shortly after the Deepwater well was capped was modeled. The comparison of simulation results to field data assesses the model's ability to explain the observed sedimentation event and tests our understanding of the main mechanisms driving such an event. The model results indicate that diatom carbon and oil compounds captured in the trap were linked to a sedimentation event that reached peak intensity just before the trap was deployed. The model simulations predict the measured sedimentation rates of oil compounds and organic carbon reasonably well, indicating that the key mechanisms driving this process were captured by the model. In the baseline case, which simulates the sedimentation of a large Skeletonema bloom in late August 2010, about 10% of the dispersed oil compounds lingering in the water were deposited to the seafloor. The ability of a sinking diatom bloom to scavenge dispersed oil compounds from the water column and deposit them to depth is a robust result of the model over a range of parameter variations. These results suggest that a model that combines satellite data on phytoplankton blooms with water column dispersed oil concentrations to estimate potential oil compound deposistion rates may be able to provide decision makers with guidance during an oil spill. However, additional, independent validation of the model is necessary before it can be adapted for use in an operational setting. Highlights: A model helps explain observed benthic carbon and oil depostition associated with a diatom bloom following a large oil spill. Sinking diatom blooms can transport dispersed oil in the water column to depth. The sinking diatom bloom modeled captured about 10% of the dispersed oil initially present in the water column. Short-lived phytoplankton blooms may make significant contributions to oil deposition after a spill.